2021
DOI: 10.1029/2021jf006286
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Lifespan of Hydrothermal Systems Using Thermochronology and Thermal Modeling

Abstract: Hydrothermal springs (or "hot springs") are the emergence of hot groundwater at the earth's surface (Pentecost et al., 2003;White, 1957). These springs reflect deep circulation of meteoric water that is heated in the upper ∼5 km of the earth's crust and are thought to reflect geothermal anomalies and zones of enhanced crustal permeability (Ferguson & Grasby, 2011;Grasby & Hutcheon, 2001). These systems offer vital information of a region's hydrological, climatic and tectonic histories (Gao et al., 2013;Grasby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Elucidating past hydrothermal activity is also an important target of thermochronology. For example, a growing number of studies have applied thermochronometry to detect thermal anomalies derived from uid activity along fault zones (e.g., Tagami et al, 2001;Murakami et al, 2002;Tagami and Murakami, 2007;Wöl er et al, 2010;Ault et al, 2016;Milesi et al, 2019Milesi et al, , 2020Louis et al, 2019;Jess et al, 2021). Furthermore, a number of studies have reported thermal anomalies and cooling dates related to ore-forming uids (e.g., Arne et al, 1990;Wilson et al, 2003;Yuan et al, 2009;Márton et al, 2010;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating past hydrothermal activity is also an important target of thermochronology. For example, a growing number of studies have applied thermochronometry to detect thermal anomalies derived from uid activity along fault zones (e.g., Tagami et al, 2001;Murakami et al, 2002;Tagami and Murakami, 2007;Wöl er et al, 2010;Ault et al, 2016;Milesi et al, 2019Milesi et al, , 2020Louis et al, 2019;Jess et al, 2021). Furthermore, a number of studies have reported thermal anomalies and cooling dates related to ore-forming uids (e.g., Arne et al, 1990;Wilson et al, 2003;Yuan et al, 2009;Márton et al, 2010;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…, 2019;Jess et al, 2021). Furthermore, a number of studies reported thermal anomalies and cooling dates related to ore-forming uids (e.g.,Arne et al, 1990;Wilson et al, 2003;Yuan et al, 2009;Márton et al, 2010;Wang …”
mentioning
confidence: 99%